Determinants of cesarean delivery in Indonesia: An analysis of the 2017 Indonesia demographic and health survey - Dinda Dwi Fajarwati; Nurhalina Sari (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: According to a statement by the World Health Organization (WHO), the optimal proportion of sectio caesarea (SC) is considered to be between 10-15%. In Indonesia, based on survey data for deliveries using the sectio caesarea (SC) method, the cases increased from 9.8% in 2013 and 17.6% in 2018.Purpose: To determinants of cesarean delivery in Indonesia: An analysis of the 2017 Indonesia demographic and health surveyMethod: This type of research is a quantitative study with a cross-sectional design. The population and sample in this study were 14,087 women of childbearing age 15-49 years who had complete variables. Data analysis used chi-square and multiple logistic regression.Results: Found that there was a significant relationship between sectio caesarea with maternal age, mother's occupation, wealth index, place of residence, spouse's occupation, partner's education, type of birth, history of ANC visits, baby size, health facilities, history of pregnancy complications and delivery, history of miscarriage with p-value < 0,001. And there is no relationship between sectio caesarea and maternal education with a p-value of 0.862. The dominant factor that affects mothers giving birth by cesarean section is the type of birth with an OR of 2.854 times (CI 95% 1,932 – 4,206).Suggestion: It is expected that people who have undergone IVF or pregnancy insemination will carry out the fertilization alone in order to reduce the risk of giving birth by cesarean section and women who are already pregnant with multiple pregnancies are expected to be more diligent in conducting ante-natal care visits so that they can better detect the progress of their pregnancy and prevent complications. which will allow delivery by cesarean section.